2021
DOI: 10.1007/s12072-021-10268-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a prognostic model for hepatitis B virus‑related acute-on-chronic liver failure patients with bacterial infection

Abstract: Background Bacterial infection is one of the most frequent complications in acute-on-chronic liver failure (ACLF), which leads to high mortality. However, a specific prognostic model for ACLF patients with bacterial infection has not been well established. Aim To establish and validate a nomogram for predicting 30-day mortality of hepatitis B virus-related ACLF (HBV-ACLF) patients with bacterial infection. Methods A total of 513 ACLF patients for HBV reactivation were enrolled in the prospective cohort, and 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…and positive urine culture; or at least 2 of the above presentations and more than 10 leukocytes/μL in urine. (iv)bacteremia: positive blood culture ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…and positive urine culture; or at least 2 of the above presentations and more than 10 leukocytes/μL in urine. (iv)bacteremia: positive blood culture ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a CCL 4 -induced ALI mouse model, the effects of EVs released from hepatocytes and other non-parenchymal cells on hepatic macrophages were explored, indicating that EVs play a pivotal role in liver regeneration by depolarizing MoMF and inducing Kuffer cells to M2-type ( 58 , 59 ). Although M2-like macrophage response promotes injured liver repair and regeneration, the immune suppressive mediators released into the circulation can be harmful and lead to immune-compromised status, therefore increasing the susceptibility to infections, even immune paresis in sepsis in PALF ( 60 62 ). Therefore, immune evaluation for children with indeterminate, progressive hepatitis or indeterminate ALF should be carried out, including assessments for T cell activation, macrophage activation, NK cell function, and other serum biochemical markers ( 63 ).…”
Section: Immune Activation In Acute Liver Injury/failurementioning
confidence: 99%
“…Zhang Z and Rui et al reported that two predictive models (one named GIC including serum globulin, IL-6, and CRP; the other model including albumin, CRP, and glucose) can predict the bacterial infection development in HBV-ACLF patients 6 , 7 . Furthermore, some parameters, such as age, total bilirubin, lactate dehydrogenase, soluble IL-2 receptor, WBC count, etc., were also identified as independent predictors for mortality in ACLF patients with infection 8 , 9 . However, besides immune-inflammatory responses 10 , 11 , hypermetabolism and coagulation dysfunction lacking attention have already existed at a very early stage of infection 12 , 13 .…”
Section: Introductionmentioning
confidence: 96%